Occurrence of Chlorpyrifos Residues in Milk of Terai Region of Uttarakhand, India - Karabasanavar, Nagappa S; Singh, Suresh P (Indian Journal of Dairy Science, 2012)
Pesticides are used in plant protection and public health to defend against pests. But, the harmful residues that enter the food chain are of great health concerns. Keeping in view application of chlorpyrifos in agriculture and allied fields, the present study was aimed at the determination of its residues in milk. Residual concentrations of chlorpyrifos were determined in milk collected from different locations of Tarai and Kumaon regions of Uttarakhand state. Sample extraction was carried out using liquid-liquid partition followed by clean up using alumina column chromatographic and quantification of the residues was undertaken with high performance liquid chromatography (HPLC). Of the total 170 milk samples collected, 4.7% samples showed chlorpyrifos residues with the mean residual concentration of 0.092 Î¼g mL-1; of which most of them were found to contain residues above the prescribed maximum permissible limit (MRL) of 0.02 mg kg-1. Since chlorpyrifos residues have health and environmental issues, hence farmers must be educated about their judicious use.